Entrepreneurship Education in Higher Education as an Alternative to Reduce Educated Unemployed in Indonesia - Meyli Khusna Yuliana; Mararti Mararti; Nur Ulil Absoriah (Universitas Sebelas Maret, 2019)
This article aims as an effort that can be done to overcome the increasing educated unemployment by preparing college graduates who are not only oriented to job seekers but also as job creation. The research method used is literature study, data collection is carried out using a study of books, literature, notes, reports, and the internet which has to do with the problem being solved. The sources of literature in this study were obtained from books, journals, and research results (thesis, thesis, dissertation) so that this article covers general processes such as systematically identifying theories, library discoveries and analytical documents related to research topics. The expected outcome is in the form of learning methods about entrepreneurship that can be developed in higher education as an alternative to entrepreneurship development for students.